Perlambatan migrasi sirkuler: Penilaian terhadap perubahan pola migrasi sirkuler di pedesaan Jawa - Agung Wicaksono; Ardana Kusumawanto (Jurnal Kependudukan Indonesia, 2021)
Circular migration has become a well-established institution for rural dwellers in Java. For farmers or unskilled rural workers, informal sectors, construction, or small trade in urban areas provide an adequate working opportunity and, at the same time, a relatively higher wage compared to the agricultural sector. It is frequently argued that migration could reduce poverty in rural areas. Although many harsh critics had been addressed to such arguments, there was relatively little attention given to the dynamics of circular migration itself, as most studies tend to argue that these activities are a constant phenomenon. Based on a comparative survey conducted in Tegal Nduwur Village in 2010 and 2020, this study finds that the rate of circular migration among farmers has significantly decreased. Better market opportunities and deindustrialisation, combined with a shifting development paradigm toward decentralisation since 1999, have gradually improved the village’s infrastructure. Under such conditions, the agroecosystem has been transformed from a slow to a fast one. The fast agroecosystem has yielded a more promising outcome for farmers’ household economy and absorbed many labor forces, i.e., people who previously migrated to various cities. This condition has decelerated the circular migration flows.